The Relationship between Family Socioeconomic Status and Online Education Usage: a Data Analysis Based on K-12 Students - Chen, Anqi (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
In this study, we explore how socioeconomic status (SES) is associated with engagement in online education among K-12 students during the COVID-19 pandemic. Based on data from the 2022 Programme of International Student Assessment, a regression analysis was used to examine the effect of household income, parental education and technology access on students’ online learning engagement. SES factors explain 48% of the variance in the dependent internet use variable, access to computer (β =0.42) and household income(β=0.55) are statistically significant predictors. Students from higher-SES families showed substantially greater engagement scores (mean = 5.4), than did students from lower-SES families (mean = 3.1, p <0.001). The study finds that reducing this digital divide is essential for mitigating educational inequalities and recommends targeted policy interventions such as affordable access to the internet, as well as increased parental support.